Destabilization of the torsioned conformation of a ligand side chain inverts the LXRβ activity - Alvarez, Lautaro Damian (2015)
Background: Liver X receptors (LXRs) are transcription factors activated by cholesterol metabolites containing an oxidized side chain. Due to their ability to regulate lipid metabolism and cholesterol transport, they have become attractive pharmacological targets. LXRs are closely related to DAF-12, a nuclear receptor involved in nematode lifespan and regulated by the binding of C-27 steroidal acids. Based on our recent finding that the lack of the C-25 methyl group does not abolish their DAF-12 activity, we evaluated the effect of removing it from the (25R)-cholestenoic acid, a LXR agonist. Methods: The binding mode and the molecular basis of action of 27-nor-5-cholestenoic acid were evaluated using molecular dynamics simulations. The biological activity was investigated using reporter gene expression assays and determining the expression levels of endogenous target genes. The in vitro MARCoNI assay was used to analyze the interaction with cofactors. Results: 27-Nor-5-cholestenoic acid behaves as an inverse agonist. This correlates with the capacity of the complex to better bind corepressors rather than coactivators. The C-25 methyl moiety would be necessary for the maintenance of a torsioned conformation of the steroid side chain that stabilizes an active LXRβ state. Conclusion: We found that a 27-nor analog is able to act as a LXR ligand. Interestingly, this minimal structural change on the steroid triggered a drastic change in the LXR response. General significance: Results contribute to improve our understanding on the molecular basis of LXRβ mechanisms of action and provide a new scaffold in the quest for selective LXR modulators.